Charge injection in an LED with a hybrid composite as the emissive layer - Gozzi, G.; Chinaglia, D. L. [UNESP]; Schmidt, T. F.; Oliveira, O. N. (Elsevier B.V., 2011)
Understanding and controlling charge transport are crucial to achieve optimized organic devices, including light emitting diodes. In this study, we investigate the charge injection in devices made with a hybrid composite (HC) containing Zn(2)SiO(4):Mn (ZSP:Mn) in a polymeric blend consisting of poly(o-methoxyaniline) (POMA) and poly(vinylidene co-trifluorethylene) P(VDFTrFE), with the architecture ITO/HC/metallic electrode (ME). Charge injection was found to depend mainly on the POMA semiconducting phase. For ITO/HC/Au, an Ohmic junction was observed because the work function of ITO is close to that of Au, which also matches the energy levels of HC. Holes are injected through the HC/Au junction, as the highest occupied molecular orbital (HOMO) level of POMA matches the Fermi level of Au. The impedance spectroscopy data for the ITO/HC/ME devices were analyzed with a theoretical model where charge injection was assumed to occur via hopping with a distribution of potential energy barriers. The average hopping distance was estimated as 5.5 angstrom and only the device with the Al electrode had the current limited by the interface mechanism (charge injection). For ITO/HC/Cu and ITO/HC/Au devices the limiting factor for the charge transport was the bulk resistance of the samples, in spite of the existence of a small interface energy barrier. The disorder parameter was 0.18 and 0.19 for the HC/Cu and HC/Al interfaces, respectively, which arises from the disordered nature of the hybrid material. The combination of the Cole-Cole model and the Miller-Abrahams function are a good approach to describe charge a.c. injection processes in disordered materials. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hybrid composite; Electroluminescent device; Charge injection; Hopping mechanisms; Impedance spectroscopy